Teacher Performance as Measured by Competence and Discipline at the State Junior High School 2 Siantar - Edy Dharma; Sherly Sherly; Humiras Betty Marlina Sihombing; Darwin Lie (Inovbiz: Jurnal Inovasi Bisnis, 2020)
The objective of this study was to determine the effect of the competence and discipline on teacher performance at the State Junior High School 2 Siantar, both simultaneously and partially. This study was conducted by using literature review and field research. The population used by the authors in this study were 39 teachers of the State Junior High School 2 Siantar. The type of data used was qualitative and quantitative data. This study used primary and secondary data sources. The data collection was carried out by questionnaires, interviews, and documentation. The analysis technique used was a quantitative descriptive analysis. The results of this study can be summarized as follows (1) there was a positive effect of competence and discipline on teacher performance; (2) there was a high correlation between competence and discipline on teacher performance; (3) the results of the study was competence and discipline has a positive and significant effect on teacher performance, both simultaneously and partially.